Quantifying the Effectiveness of Defensive Playing Styles in the Chinese Football Super League - Ruan, Lingfeng; Ge, Huanmin; Shen, Yanfei; Pu, Zhiqiang; Zong, Shouxin; Cui, Yixiong (Frontiers in Psychology, 2022)
Establishing and illustrating a predictive and prescriptive model of playing styles that football teams adopt during matches is a key step towards describing and measuring the effectiveness of styles of play. The current study aimed to identify and measure the effectiveness of different defensive playing styles for professional football teams considering the opponent’s expected goal. Event data of all 1120 matches played in the Chinese Football Super League (CSL) from the 2016 to 2020 seasons were collected, with fifteen defense-related performance variables being extracted. The PCA model (KMO=0.76) output eight factors that represented 7 different styles of play (factor 6 and 8 represent one style of play) and explained 85.17% of the total variance. An expected goal (xG) model was built using data related to 27852 shots. Finally, the xG of the opponent were calculated in the multivariate regression model, outputting five factors that (p<0.05) explained 41.6% of the total variance in the xG of the opponent and receiving a dangerous situation (factor 7) was the most apparent style (31.3%). Finally, the predicted model with defensive styles correlated with actual xG of the opponent at r = 0.62 using the 2020 season as testing data which showed that the predicted xG was correlated moderately with the actual. The result indicated that if the team strengthened the defense closed to the own goal, high intensity confrontation and defense of goalkeeper, meanwhile making less errors and receiving less dangerous situations, the xG of the opponent would be greatly reduced.